2022
DOI: 10.1136/annrheumdis-2021-222045
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of COVID-19 vaccines in patients taking immunosuppressants

Abstract: ObjectivesWe intended to assess the effectiveness of all three US Food and Drug Administration approved COVID-19 vaccines at preventing SARS-CoV-2 infection and COVID-19 hospitalisation in a large cohort of individuals on immunosuppressants for a diverse range of conditions.MethodsWe studied the effectiveness of BNT162b2 (Pfizer–BioNTech), mRNA-1273 (Moderna) and Ad26.COV2.S (Johnson & Johnson–Janssen) vaccines among individuals who take immunosuppressants (including disease-modifying antirheumatic drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 12 publications
5
35
0
1
Order By: Relevance
“…Our findings regarding vaccine effectiveness in immunosuppressed patients show a substantial reduction in effectiveness relative to previous studies that looked at the delta (B.1.617.2) variant. 5 , 6 , 7 , 8 , 9 This difference is consistent with a similar reduction in the immunocompetent population, as seen in this study and in previous work. 3 , 4 The higher effectiveness observed for the mRNA-1273 vaccine compared with the BNT162b2 vaccine is also in accordance with previous findings in people who were immunocompetent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings regarding vaccine effectiveness in immunosuppressed patients show a substantial reduction in effectiveness relative to previous studies that looked at the delta (B.1.617.2) variant. 5 , 6 , 7 , 8 , 9 This difference is consistent with a similar reduction in the immunocompetent population, as seen in this study and in previous work. 3 , 4 The higher effectiveness observed for the mRNA-1273 vaccine compared with the BNT162b2 vaccine is also in accordance with previous findings in people who were immunocompetent.…”
Section: Discussionsupporting
confidence: 93%
“… 3 , 4 Multiple studies in patients who are immunosuppressed have shown mRNA vaccines to be effective against infection and hospitalisation due to the previously dominant delta (B.1.617.2) variant, but there are few data regarding their effectiveness against the omicron variant. 5 , 6 , 7 , 8 , 9 Patients taking immunosuppressive medications have reduced immune responses following vaccination compared with immunocompetent people, but granular data about classes of immunosuppressive medications and dose level are still scarce. 10 , 11 , 12 , 13 , 14 , 15 In addition to vaccine effectiveness, there is little knowledge on how taking immunosuppressive medications affects risk of SARS-CoV-2 infection and hospitalisation due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Fully vaccinated patients, whose enrichment patterns resembled the test negatives, were more likely than those unvaccinated to be diagnosed with chronic conditions like hypertension and anxiety in the "post-COVID-19 period." This MM cohort has been extensively studied in the past 26,35,[41][42][43] , but the current study provides the longest follow-up time (over 2 years) to date and includes a "post-COVID-19 period. "…”
Section: Strengths and Principal Findingsmentioning
confidence: 99%
“…Third, these patients were immunocompromised, putting them at higher risk of severe infection and death (as high as 13%–20%) if they were to contract SARS-CoV-2. 4 , 5 …”
mentioning
confidence: 99%
“…Third, these patients were immunocompromised, putting them at higher risk of severe infection and death (as high as 13%-20%) if they were to contract SARS-CoV-2. 4,5 We hypothesize many possible reasons why the index case did not transmit to patients or other HCWs. First, the index case was wearing an N95 respirator, which may have provided superior source control compared to surgical masks.…”
mentioning
confidence: 99%